Consumer Decision Drivers in the Republic of Moldova: Choosing Recycled Clothing for a Sustainable Future - Iordachi, Victoria; Timofei, Olga; Perciun, Rodica (Calitatea Vieții, 2024)
This study evaluates consumer behaviour in the Republic of Moldova regarding the purchase of recycled clothing, aiming to identify key factors influencing these decisions. The textile sector in the EU, a major contributor to environmental impacts, highlights the urgent need for improved recycling practices and sustainable fashion. With only 1% of textiles being recycled into new garments, significant advancements in recycling technology and consumer engagement are necessary. This research utilizes a survey to assess consumer attitudes towards recycled clothing. The study examines factors such as environmental awareness, accessibility, price ‒ quality balance, and the perceived social and ecological benefits of recycled garments. Preliminary findings suggest that while awareness of environmental issues is increasing, challenges remain in terms of affordability and availability of recycled clothing. The study concludes that enhancing consumer education, improving access to recycled garments, and fostering greater participation from both businesses and consumers are essential to scaling recycling practices in Moldova. These insights aim to support the development of effective strategies to boost recycled clothing consumption and to contribute to sustainable waste management in the textile industry.